2022
DOI: 10.3389/fendo.2022.1077632
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of QRISK3 as a predictor of cardiovascular disease events in type 2 diabetes mellitus

Abstract: BackgroundThe risk of cardiovascular disease (CVD) in diabetes mellitus (DM) patients is two- to three-fold higher than in the general population. We designed a 10-year cohort trial in T2DM patients to explore the performance of QRESEARCH risk estimator version 3 (QRISK3) as a CVD risk assessment tool and compared to Framingham Risk Score (FRS).MethodThis is a single-center analysis of prospective data collected from 566 newly-diagnosed patients with type 2 DM (T2DM). The risk scores were compared to CVD devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…39 Age is an independent risk factor for both T2DM and DN. 40 The incidence of chronic renal failure increases with age in both men and women. With the aging population continuing to grow, the prevalence of older adults with chronic kidney disease is expected to rise.…”
Section: Discussionmentioning
confidence: 99%
“…39 Age is an independent risk factor for both T2DM and DN. 40 The incidence of chronic renal failure increases with age in both men and women. With the aging population continuing to grow, the prevalence of older adults with chronic kidney disease is expected to rise.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while Q-risk (QRISK®3) has been widely used as a validated tool for estimating cardiovascular risk, we found that it did not alone demonstrate a significant prediction for cardiovascular events when analyzed in isolation for patients using JAK inhibitor therapy. This suggests that Q-risk (QRISK®3) alone may not capture the full complexity of cardiovascular risk in patients with autoimmune disease using JAK inhibitor therapy [ 14 ]. These findings therefore emphasize the importance of considering additional factors, such as deprivation decile, to enhance the accuracy of risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mu et al [233] developed an algorithm to predict the risk of an acute fatal or non-fatal cardiovascular event (especially acute myocardial infarction or stroke) in the next 10 years in patients with type 2 diabetes. Thus, the QRESEARCH risk estimator version 3 is superior to the Framingham risk score by using a much larger number of clinical-paraclinical parameters and has a much higher predictability among diabetic patients [234,235].…”
Section: Predictive Risk Models For Cvd Events In Dmmentioning
confidence: 99%